Ano-rectal manometry: description of Metho-dology. Determination of Anal High Pressure Zone - Santurtún, Paz; Balboa, Oscar; Voelker, Ricardo; Ricciardi, Norma (Cirugía del Uruguay, 1980)
Report on search for a safe technique in recto -anal manometry which has lead to development of a methodology coBsisting in withdrawal of registering element at constant speed. By the employment of this technique they define the anal high pressure zone (AHPZ) with normal manometric characteristics and the RAIR (recto - anal inhibition reflex) wich is the objetive of procedure.